Titanium dioxide nanorod array film and preparation method thereof

By preparing TiO2 nanorod array thin films, the nanoparticle density in the TiO2 seed layer is controlled by hydrolysis reaction, which solves the problem of difficulty in controlling the nanorod density in traditional technology, and achieves precise regulation of the performance of optoelectronic devices.

CN119504147APending Publication Date: 2025-02-25HEFEI INSTITUTE OF PHYSICAL SCIENCE CHINESE ACADEMY OF SCIENCES
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411736839.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

Traditional technology is difficult to control nanorod density without changing the length and diameter of TiO2 nanorods, limiting the precise regulation of the performance of optoelectronic devices based on TiO2 nanorod arrays.

Method used

A clear and transparent precursor solution was prepared by mixing titanate, hydrolysis inhibitor and organic solvent. After coating the precursor film, the hydrolysis reaction was carried out to control the hydrolysis reaction conditions to regulate the nanoparticle density in the TiO2 seed layer, thereby forming a TiO2 nanorod array layer in the hydrothermal method to achieve precise regulation of the nanorod density.

Benefits of technology

Without changing the length and diameter of the nanorods, precise control of the nanorod density in the TiO2 nanorod array layer is achieved by regulating the hydrolysis reaction conditions, thereby optimizing the photoelectric performance of the optoelectronic devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119504147A_ABST
    Figure CN119504147A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of optoelectronic devices, in particular to a titanium dioxide nanorod array film and a preparation method thereof. The preparation method of the titanium dioxide nanorod array film comprises the following steps: mixing titanate, a hydrolysis inhibitor and an organic solvent to obtain a precursor solution; coating a substrate with the precursor solution to obtain a precursor film; carrying out hydrolysis reaction on the precursor film, and carrying out sintering treatment to obtain a titanium dioxide seed layer; and forming a titanium dioxide nanorod array layer on the titanium dioxide seed layer by using a hydrothermal method. According to the preparation method provided by the invention, the density of the nanorods in the TiO2 nanorod array layer can be regulated and controlled on the premise of not changing the length and diameter of the nanorods, so that the photoelectric property of the TiO2 nanorod array film is precisely regulated and controlled.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of optoelectronic devices, and in particular to a titanium dioxide nanorod array film and a preparation method thereof. Background Art

[0002] Titanium dioxide (TiO2) is a safe, green and stable semiconductor material. Its morphology has an important influence on the optical, electrical and chemical properties of TiO2 materials. At present, TiO2 nanomaterials with morphological structures such as nanoparticles, nanosheets, nanotubes and nanorods have been developed and widely used in photocatalysis, photovoltaics and energy storage. Among them, TiO2 nanorod arrays are composed of TiO2 nanorods grown vertically on the substrate surface. They have a special photon confinement effect and a direct electron transmission channel. They have been used to prepare high-efficiency solar cells, energy storage devices and photocatalytic hydrogen production electrodes. The length, diameter and number density of nanorods in TiO2 nanorod arrays have a significant impact on their photoelectric properties. However, it is difficult to control the density of nanorods without changing the length and diameter in traditional technologies, which seriously limits the precise regulation of the performance of optoelectronic devices based on TiO2 nanorod arrays. Summary of the invention

[0003] Based on this, it is necessary to provide a titanium dioxide nanorod array film and a preparation method thereof to solve the problem that it is difficult to control the density of nanorods without changing the length and diameter in traditional technology, which seriously limits the precise regulation of the performance of optoelectronic devices based on TiO2 nanorod arrays.

[0004] The above-mentioned purpose of the present application is achieved through the following technical solutions:

[0005] In a first aspect of the present application, a method for preparing a titanium dioxide nanorod array thin film is provided, comprising the following steps:

[0006] mixing titanate, a hydrolysis inhibitor and an organic solvent to obtain a precursor solution;

[0007] coating the precursor solution on a substrate to obtain a precursor film;

[0008] The precursor film is subjected to a hydrolysis reaction and sintering treatment to obtain a titanium dioxide seed layer;

[0009] A titanium dioxide nanorod array layer is formed on the titanium dioxide seed layer by a hydrothermal method.

[0010] In one embodiment, the precursor film is subjected to a hydrolysis reaction, comprising the following steps:

[0011] The precursor film is placed in an environment with a relative humidity of 80% to 90% and a temperature of 10° C. to 40° C. for hydrolysis for 1 h to 32 h.

[0012] In one embodiment, the titanate includes one or more of n-butyl titanate, n-propyl titanate, isopropyl titanate and ethyl titanate.

[0013] In one embodiment, the hydrolysis inhibitor includes one or more of acetic acid, hydrochloric acid and nitric acid.

[0014] In one embodiment, the organic solvent includes one or more of ethanol, methanol and isopropanol.

[0015] In one embodiment, the volume ratio of the titanate, the hydrolysis inhibitor and the organic solvent is 1:(0.05-0.2):(2-5).

[0016] In one embodiment, the sintering temperature of the sintering treatment is 450° C. to 550° C., the sintering time is 0.5 h to 2 h, and the sintering atmosphere is an oxidizing atmosphere.

[0017] In one embodiment, the crystal form of the nanoparticles in the titanium dioxide seed layer is anatase titanium dioxide.

[0018] In one embodiment, the particle size of the nanoparticles in the titanium dioxide seed layer is 10 nm to 30 nm.

[0019] In one embodiment, the thickness of the titanium dioxide seed layer is 50 nm to 150 nm.

[0020] In one embodiment, the hydrothermal method comprises the following steps:

[0021] mixing a titanium source and an acid solution to obtain a hydrothermal reaction solution;

[0022] The titanium dioxide seed layer is placed in the hydrothermal reaction solution to perform a hydrothermal reaction.

[0023] In one embodiment, the titanium source includes one or more of n-butyl titanate, n-propyl titanate, isopropyl titanate and ethyl titanate.

[0024] In one embodiment, the acid in the acid solution includes one or more of hydrochloric acid, nitric acid and acetic acid, and the concentration is 1 mol / L to 10 mol / L.

[0025] In one embodiment, the volume ratio of the titanium source to the acid solution is (0.5-1.5): (20-80).

[0026] In one embodiment, the reaction temperature of the hydrothermal reaction is 150° C. to 200° C., and the reaction time is 1 h to 5 h.

[0027] In one embodiment, the nanorods in the titanium dioxide nanorod array layer meet the following requirements: length of 200nm~1000nm, diameter of 30nm~60nm, density of 10μm -2 ~200μm -2 .

[0028] In a second aspect of the present application, a titanium dioxide nanorod array film is provided, which is prepared by the method for preparing a titanium dioxide nanorod array film as described above.

[0029] This application has at least the following beneficial effects:

[0030] The present application utilizes titanate, hydrolysis inhibitor and organic solvent to prepare a clear, transparent and stable precursor solution, and the precursor solution will not be converted into a sol containing colloidal particles with larger particle size. After the precursor solution is coated to form a precursor film and then subjected to a hydrolysis reaction, the particle size of the nanoparticles in the TiO2 seed layer can be regulated by controlling the conditions of the hydrolysis reaction, thereby regulating the density of the nanorods in the TiO2 nanorod array layer without changing the length and diameter of the nanorods, thereby achieving precise regulation of the photoelectric properties of the TiO2 nanorod array film. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] In order to more clearly illustrate the technical solutions in the embodiments of the present application and to more completely understand the present application and its beneficial effects, the following is a brief introduction to the drawings required for the description of the embodiments. Obviously, the drawings described below are only some embodiments of the present application, and those skilled in the art can obtain other drawings based on these drawings without creative work.

[0032] Figure 1 is a schematic diagram of a process for preparing a TiO2 nanorod array film in an embodiment;

[0033] Figure 2 is a schematic structural diagram of a TiO2 nanorod array film in one embodiment;

[0034] Figure 3 XRD diagram of the TiO2 seed layer in Examples 2 to 4;

[0035] Figure 4 is a SEM image of the TiO2 seed layer in Example 2; wherein, Figure 4 Figure (a) is the surface image. Figure 4 Figure (b) is a cross-sectional image;

[0036] Figure 5 is a SEM image of the TiO2 seed layer in Example 3; wherein, Figure 5 Figure (a) is the surface image. Figure 5 Figure (b) is a cross-sectional image;

[0037] Figure 6 is a SEM image of the TiO2 seed layer in Example 4; wherein, Figure 6 Figure (a) is the surface image. Figure 6 Figure (b) is a cross-sectional image;

[0038] Figure 7 is the XRD pattern of the TiO2 nanorod array layer in Examples 2 to 4;

[0039] Figure 8 is a SEM image of the TiO2 nanorod array layer in Example 2; wherein, Figure 8 Figure (a) is the surface image. Figure 8 Figure (b) is a cross-sectional image;

[0040] Fig. 9 is a SEM image of the TiO2 nanorod array layer in Example 3; wherein, Fig. 9 Figure (a) is the surface image. Fig. 9 Figure (b) is a cross-sectional image;

[0041] Fig.10 is a SEM image of the TiO2 nanorod array layer in Example 4; wherein, Fig.10 Figure (a) is the surface image. Fig.10 Figure (b) is a cross-sectional image;

[0042] Fig.11 is a HRTEM image of the TiO2 nanorod array layer of Example 3;

[0043] Fig.12 This is a current-voltage relationship curve of the solar cell in Example 10.

[0044] Reference numerals: substrate 10 , glass layer 11 , conductive layer 12 , TiO 2 seed layer 20 , TiO 2 nanorod array layer 30 . DETAILED DESCRIPTION

[0045] In order to facilitate the understanding of the present application, the present application is further described in detail below in conjunction with specific embodiments. However, the present application can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present application more thorough and comprehensive.

[0046] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which this application belongs. The terms used herein in the specification of this application are only for the purpose of describing specific embodiments and are not intended to limit this application.

[0047] In the present application, the meaning of "and / or" includes any and all combinations of one or more related listed items. "At least one" means more than one, such as one, two and more than two. "Multiple" or "several" means at least two, such as two, three, etc., and "multi-layer" means at least two layers, such as two layers, three layers, etc., unless otherwise clearly and specifically defined. In the description of the present application, "several" means at least one, such as one, two, etc., unless otherwise clearly and specifically defined.

[0048] When a numerical range is disclosed in this application, the above range is considered to be continuous and includes the minimum and maximum values ​​of the range, as well as every value between such minimum and maximum values. Further, when a range refers to an integer, every integer between the minimum and maximum values ​​of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be combined. In other words, unless otherwise indicated, all ranges disclosed in this application should be understood to include any and all subranges included therein.

[0049] Unless otherwise specified, all steps of the present application may be performed sequentially or randomly. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may also include step (c), which means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.

[0050] In this application, "above" or "below" includes the number itself. For example, "1 below" includes 1.

[0051] The temperature parameters in this application, unless otherwise specified, are allowed to be either constant temperature treatment or to vary within a certain temperature range. It should be understood that the constant temperature treatment allows the temperature to fluctuate within the accuracy range controlled by the instrument. Fluctuations within the range of ±5°C, ±4°C, ±3°C, ±2°C, and ±1°C are allowed.

[0052] In the present application, room temperature refers to indoor temperature, normal temperature or general temperature. Generally speaking, the range of room temperature can be any one of the following temperature intervals: 23°C ± 2°C, 25°C ± 5°C or 20°C ± 5°C.

[0053] In the present application, unless otherwise specified, the basis of the percentages (including weight percentages) in the present application is the total weight of the composition, "wt%" means mass percentage, "vol%" means volume percentage, and "at%" means atomic percentage.

[0054] In the present application, unless otherwise specified, each reaction step may be carried out in the order described herein or may not be carried out in the order described herein. For example, each reaction step may include other steps, and the order of the reaction steps may also be appropriately changed.

[0055] the term

[0056] Unless otherwise specified or incompatible herewith, the terms and phrases used herein shall have the following meanings:

[0057] Nanorod density: the number of nanorods grown per unit area, in μm -2 、cm -2 、mm -2 or m -2 As an example, 100 μm -2 Indicates that the area is 1μm 2 There are 100 nanorods grown on the substrate.

[0058] The length, diameter and density of the nanorods in the TiO2 nanorod array have a significant impact on its photoelectric properties. It is relatively simple to regulate the length and diameter of the nanorods, but there is a lack of effective methods to regulate the density of the nanorods without affecting the length and diameter.

[0059] In traditional technology, there are two main methods to control the density of nanorods: (1) changing the conditions such as the concentration of reactants, reaction temperature and reaction time in the hydrothermal reaction. Although this method changes the number density of nanorods, it also changes the length and diameter of the nanorods, making it difficult to accurately control the overall photoelectric performance of the array film. (2) Photolithography of the TiO2 seed layer to prepare a certain number of nucleation sites on the substrate, and then in situ growth of nanorod arrays on these nucleation sites. However, the cost of the photolithography process is expensive, and this method can usually only control the seed layer density at the micron level, but not at the nanometer level. The obtained TiO2 nanorod array film is usually a nanocluster film with a gap of several microns, rather than a uniform nanorod array film.

[0060] It can be seen that traditional technology still lacks a simple and effective method to control the density of nanorods in TiO2 nanorod arrays without changing the length and diameter of the nanorods, which makes it difficult to achieve precise control of the performance of optoelectronic devices based on titanium dioxide nanorod arrays.

[0061] Based on this, in the first aspect of the present application, a method for preparing a TiO2 nanorod array film is provided to solve the problem in traditional technology that it is difficult to control the density of nanorods without changing the length and diameter.

[0062] See also Figure 1 and Figure 2 ,in, Figure 1 FIG. 1 is a schematic diagram of a process for preparing a TiO2 nanorod array thin film in an embodiment. Figure 2 FIG. 1 is a schematic diagram of the structure of a TiO2 nanorod array film in an embodiment. Figure 1 As shown, the method for preparing the TiO2 nanorod array film comprises the following steps:

[0063] S1: mixing titanate, hydrolysis inhibitor and organic solvent to obtain a precursor solution;

[0064] S2: coating the precursor solution on the substrate 10 to obtain a precursor film;

[0065] S3: hydrolyzing the precursor film and sintering it to obtain a TiO2 seed layer 20;

[0066] S4: forming a TiO 2 nanorod array layer 30 on the TiO 2 seed layer 20 by a hydrothermal method.

[0067] The present application utilizes titanate, hydrolysis inhibitor and organic solvent to prepare a clear, transparent and stable precursor solution, and the precursor solution will not be converted into a sol containing colloidal particles with larger particle size. After being coated to form a precursor film and then subjected to a hydrolysis reaction, the density of nanoparticles in the TiO2 seed layer 20 can be regulated by controlling the conditions of the hydrolysis reaction, thereby regulating the density of nanorods in the TiO2 nanorod array layer 30 without changing the length and diameter of the nanorods, thereby achieving precise regulation of the photoelectric properties of the TiO2 nanorod array film.

[0068] The following is a detailed description of the preparation method of TiO2 nanorod array film by step description.

[0069] S1: mixing titanate, a hydrolysis inhibitor and an organic solvent to obtain a precursor solution.

[0070] In traditional technology, water is usually added to the precursor solution. During the stirring process, titanium ions react with hydroxide ions to form titanium hydroxide, and agglomerate to form colloidal particles with larger particle sizes, so that the precursor solution is converted into a sol. Since the sol has been fully hydrolyzed, after it is coated into a film, the properties of the seed layer cannot be regulated by changing the conditions of the hydrolysis reaction. That is, the thickness and particle size of the seed layer are usually determined by the properties of the sol. Therefore, the properties of the seed layer can be regulated by changing the reactants and their concentrations of the sol, thereby regulating the density of the nanorods, but the length and diameter of the nanorods will also change accordingly.

[0071] In response to the above findings, the present application utilizes titanate, hydrolysis inhibitor and organic solvent to prepare a clear, transparent and stable precursor solution. The precursor solution does not contain water and will not hydrolyze to form a sol containing colloidal particles. After coating it into a film, the particle size of the TiO2 seed layer 20 can be regulated by the hydrolysis reaction, thereby precisely controlling the density of the nanorods without changing the length and diameter of the nanorods.

[0072] Optionally, the titanate includes one or more of n-butyl titanate, n-propyl titanate, isopropyl titanate and ethyl titanate, and further may be n-butyl titanate.

[0073] Optionally, the hydrolysis inhibitor includes one or more of acetic acid, hydrochloric acid and nitric acid, further optionally acetic acid, and further optionally glacial acetic acid, ie, anhydrous acetic acid.

[0074] Optionally, the organic solvent includes one or more of ethanol, methanol and isopropanol, further may be ethanol, and further may be anhydrous ethanol.

[0075] Optionally, the titanate, the hydrolysis inhibitor and the organic solvent each independently satisfy: a water content ≤ 0.5%; further optionally, a water content ≤ 0.1%.

[0076] It can be understood that the water content refers to the mass fraction of water in the chemical reagent. By controlling the water content in the titanate, catalyst and organic solvent, the water content in the precursor solution can be reduced as much as possible, and the hydrolysis and agglomeration of titanium ions to form colloidal particles can be avoided as much as possible, which is conducive to the precise control of the properties of the subsequent TiO2 seed layer 20 and the TiO2 nanorod array layer 30. In addition, in order to avoid the influence of water vapor in the air on the precursor solution, the precursor solution needs to be prepared and used immediately, or stored in a water-free environment after preparation, such as in a vacuum drying oven or a glove box.

[0077] Optionally, the volume ratio of the titanate, the hydrolysis inhibitor and the organic solvent is 1:(0.05-0.2):(2-5). As an example, the volume ratio of the titanate and the hydrolysis inhibitor is 1:(0.05-0.2), such as 1:0.05, 1:0.06, 1:0.07, 1:0.08, 1:0.09, 1:0.1, 1:0.12, 1:0.14, 1:0.16, 1:0.18 or 1:0.2, and further optionally 1:0.1; the volume ratio of the titanate and the organic solvent is 1:(2-5), such as 1:2, 1:2.5, 1:3, 1:3.5, 1:4, 1:4.5 or 1:5, and further optionally 1:4.

[0078] Under the condition that the volume ratio of titanate, hydrolysis inhibitor and organic solvent is the same, the particle size of TiO2 seed layer 20 can be adjusted by changing the time of hydrolysis reaction, thereby changing the density of nanorods under the condition that the length and diameter of nanorods remain unchanged. That is to say, if the volume ratio of each reactant in the precursor solution of the present application falls within the above range and keeps the volume ratio consistent, the density of nanorods can be adjusted by changing the time of hydrolysis reaction, and the length and diameter of nanorods remain unchanged.

[0079] S2: coating the precursor solution on the substrate 10 to obtain a precursor film.

[0080] Optionally, the substrate 10 includes one or more of a glass substrate, a silicon substrate, a metal substrate and a metal oxide substrate. Among them, the glass substrate includes one or more of a conductive glass substrate and a non-conductive glass substrate; the silicon substrate includes one or more of a single crystal silicon substrate and a polycrystalline silicon substrate, and the silicon substrate may be doped with non-metallic elements such as boron or phosphorus; the material of the metal substrate includes one or more of titanium, copper, iron, aluminum, gold, silver and platinum; the material of the metal oxide substrate includes one or more of aluminum oxide (or sapphire), zinc oxide and gallium oxide.

[0081] Further optionally, the substrate 10 is a conductive glass substrate, which is conducive to the preparation of high-performance optoelectronic devices. The conductive glass substrate includes a glass layer 11 and a conductive layer 12 disposed on the glass layer 11. The material of the glass layer 11 includes one or more of quartz glass, borosilicate glass, soda glass, potassium glass, lead glass and aluminum-magnesium glass, and the material of the conductive layer 12 includes one or more of fluorine-doped tin oxide (FTO), indium tin oxide (ITO), aluminum zinc oxide (AZO), indium zinc oxide (IZO), indium gallium zinc oxide (IGZO), indium gallium tin oxide (IGTO), indium zinc tin oxide (IZTO) and indium gallium zinc tin oxide (IGZTO). In some specific examples, the substrate 10 is a FTO glass substrate.

[0082] Optionally, before the step of coating the precursor solution on the substrate 10, a step of cleaning the substrate 10 is also included. The method of cleaning the substrate 10 includes ultrasonic cleaning, the medium of ultrasonic cleaning includes one or more of ethanol, isopropanol, acetone and water, the water can be deionized water, pure water or ultrapure water, the number of ultrasonic cleaning can be 1 to 5 times, and the time of each ultrasonic cleaning is independently 3 minutes to 10 minutes.

[0083] Optionally, the method of coating the precursor solution on the substrate 10 includes one or more of spin coating, spray coating, blade coating, drip coating and dipping, and further can be spin coating. The conditions of the spin coating method include: the spin coating speed is 2000rpm~4000rpm, the spin coating time is 15s~60s, the amount of the precursor solution is 0.05mL / cm 2 ~0.2mL / cm 2 The number of spin coating can be 1 to 3 times.

[0084] As an example, in the spin coating method, the spin coating speed can be 2000rpm, 2200rpm, 2400rpm, 2600rpm, 2800rpm, 3000rpm, 3200rpm, 3400rpm, 3600rpm, 3800rpm or 4000rpm; the spin coating time can be 15s, 20s, 25s, 30s, 35s, 40s, 45s, 50s, 55s or 60s; the amount of the precursor solution can be 0.05mL / cm 2 , 0.08mL / cm 2 , 0.1mL / cm 2 , 0.12mL / cm 2 , 0.15mL / cm 2 、0.18mL / cm 2 or 0.2mL / cm 2 ; The number of spin coating can be 1 time, 2 times or 3 times.

[0085] S3: subjecting the precursor film to a hydrolysis reaction and a sintering treatment to obtain a TiO2 seed layer 20.

[0086] Optionally, the precursor film is subjected to a hydrolysis reaction, comprising the following steps: placing the precursor film in an environment with a relative humidity of 80% to 90% and a temperature of 15° C. to 40° C. for hydrolysis for 1 hour to 32 hours.

[0087] As an example, the relative humidity during the hydrolysis reaction can be 80%, 81%, 82%, 83%, 84%, 85%, 86%, 87%, 88%, 89% or 90%; the hydrolysis temperature can be 15°C, 18°C, 20°C, 22°C, 25°C, 28°C, 30°C, 32°C, 35°C, 38°C or 40°C, and can be further selected as 20°C~25°C; the hydrolysis time can be 1h, 2h, 4h, 8h, 12h, 16h, 20h, 24h, 28h or 32h, and can be further selected as 1h~24h.

[0088] In the present application, hydrolysis is carried out in a high humidity environment, which can promote the hydrolysis of titanium ions and accelerate the reaction rate of hydrolysis. If the relative humidity is too low, the hydrolysis process is slow; if the relative humidity is too high, the hydrolysis rate is too fast, and it is difficult to control the appropriate hydrolysis time window. Under the condition that the precursor solution, spin coating process, relative humidity and hydrolysis temperature are kept consistent, as the hydrolysis time increases, the particle size of the nanoparticles of the TiO2 seed layer 20 gradually decreases, so that the density of the nanorods grown on the TiO2 seed layer 20 also decreases, and the length and diameter of the nanorods do not change significantly.

[0089] Optionally, the sintering temperature of the sintering treatment is 450° C. to 550° C., the sintering time is 0.5 h to 2 h, and the sintering atmosphere is an oxidizing atmosphere.

[0090] As an example, the sintering temperature of the sintering treatment can be 450℃, 460℃, 470℃, 480℃, 490℃, 500℃, 510℃, 520℃, 530℃, 540℃ or 550℃, and can be further selected as 500℃~550℃; the sintering time can be 0.5h, 0.8h, 1h, 1.2h, 1.5h, 1.8h or 2h, and can be further selected as 0.5h~1h; the sintering atmosphere can be an air atmosphere or an oxygen atmosphere, and can be further selected as an air atmosphere.

[0091] It can be understood that after the hydrolysis reaction, sintering at 450° C. to 550° C. for 0.5 h to 2 h will hardly affect the particle size of the nanoparticles of the TiO 2 seed layer 20 , and thus the density of the nanorods will not change significantly.

[0092] Optionally, the crystal form of the nanoparticles in the TiO2 seed layer 20 is anatase titanium dioxide.

[0093] Optionally, the particle size of the nanoparticles in the TiO2 seed layer 20 is 10 nm to 30 nm;

[0094] Optionally, the thickness of the TiO 2 seed layer 20 is 50 nm to 150 nm, for example, 50 nm, 60 nm, 70 nm, 80 nm, 90 nm, 100 nm, 110 nm, 120 nm, 130 nm, 140 nm or 150 nm.

[0095] S4: forming a TiO 2 nanorod array layer 30 on the TiO 2 seed layer 20 by a hydrothermal method.

[0096] Optionally, the hydrothermal method includes the following steps: mixing a titanium source and an acid solution to obtain a hydrothermal reaction solution; placing the titanium dioxide seed layer in the hydrothermal reaction solution to perform a hydrothermal reaction.

[0097] Optionally, the titanium source includes one or more of n-butyl titanate, n-propyl titanate, isopropyl titanate and ethyl titanate, and further may be isopropyl titanate.

[0098] Optionally, the acid in the acid solution includes one or more of hydrochloric acid, nitric acid and acetic acid, and the concentration is 1 mol / L to 10 mol / L. Further optionally, the acid solution is a hydrochloric acid (HCl) solution, and its preparation method includes the following steps: mixing concentrated hydrochloric acid and water in a volume ratio of 1:1 to obtain a hydrochloric acid solution; wherein the mass fraction of the concentrated hydrochloric acid is 36% to 38%, the concentration is about 12 mol / L, and the water can be pure water, ultrapure water or deionized water.

[0099] Optionally, the volume ratio of the titanium source to the acid solution is (0.5-1.5):(20-80). As an example, the volume ratio of the titanium source to the acid solution can be 0.5:20, 0.5:40, 0.5:60, 0.5:80, 1:20, 1:40, 1:60, 1:80, 1.5:20, 1.5:40, 1.5:60 or 1.5:80, and can further be 0.5:40.

[0100] Optionally, the reaction temperature of the hydrothermal reaction is 150°C to 200°C, and the reaction time is 1h to 5h. As an example, the reaction temperature of the hydrothermal reaction can be 150°C, 160°C, 170°C, 180°C, 190°C or 200°C, and the reaction time of the hydrothermal reaction can be 1h, 2h, 3h, 4h or 5h; the hydrothermal reaction is carried out under sealed conditions, such as a reactor.

[0101] It is understandable that the length of the nanorods can be changed by changing at least one of the conditions of the hydrothermal reaction solution, the reaction temperature of the hydrothermal reaction, and the reaction time to obtain better photoelectric performance. After determining the optimal value or optimal range of the length of the nanorods, the density of the nanorods can be further changed by using the time change of the hydrolysis reaction during the preparation of the TiO2 seed layer.

[0102] Optionally, after the hydrothermal reaction, the following steps are further included: taking out the substrate 10 on which the TiO2 seed layer 20 and the TiO2 nanorod array layer 30 are grown, rinsing with sufficient water and ethanol, and drying to obtain a TiO2 nanorod array film.

[0103] Optionally, the nanorods in the TiO2 nanorod array layer 30 meet the following requirements: length of 200nm-1000nm, diameter of 30nm-60nm, density of 20μm -2 ~200μm -2 As an example, the length of the nanorods may be 200 nm, 300 nm, 400 nm, 500 nm, 600 nm, 700 nm, 800 nm, 900 nm, or 1000 nm; the diameter of the nanorods may be 30 nm, 35 nm, 40 nm, 45 nm, 50 nm, 55 nm, or 60 nm; the density of the nanorods may be 20 μm -2 , 40μm -2 、60μm -2 、80μm -2 , 100μm -2 , 120μm -2 、140μm -2 、160μm -2 、180μm -2 or 200 μm -2 ; The crystal form of the nanorods in the TiO2 nanorod array layer 30 is rutile TiO2.

[0104] In a second aspect of the present application, a titanium dioxide nanorod array film is provided, which is prepared by the method for preparing a titanium dioxide nanorod array film as described above.

[0105] like Figure 2 As shown, the TiO2 nanorod array film includes a substrate 10, a TiO2 seed layer 20 and a TiO2 nanorod array layer 30 which are stacked in sequence.

[0106] In a third aspect of the present application, an optoelectronic device is provided, comprising the titanium dioxide nanorod array film as described above, or comprising a titanium dioxide nanorod array film prepared by the method for preparing the titanium dioxide nanorod array film as described above.

[0107] The following is further described in conjunction with specific examples and comparative examples. The raw materials involved in the following specific examples, unless otherwise specified, can all be sourced from commercial sources. The instruments used, unless otherwise specified, can all be sourced from commercial sources. The processes involved, unless otherwise specified, are all routinely selected by those skilled in the art.

[0108] Example 1

[0109] Please refer to Table 1. The preparation method of the TiO2 nanorod array film in this embodiment is as follows:

[0110] (1) Cleaning the substrate:

[0111] The substrate is a FTO glass substrate, which is placed in acetone, isopropanol and ultrapure water in sequence, ultrasonicated for 5 minutes respectively, and dried for later use.

[0112] (2) Preparation of TiO2 seed layer:

[0113] n-Butyl titanate, glacial acetic acid and anhydrous ethanol were mixed in a volume ratio of 1:0.1:4 to prepare a clear and transparent precursor solution. The precursor solution was spin-coated on the substrate twice, with a spin coating speed of 3000 rpm and a spin coating time of 20 s each time. The amount of the precursor solution was 0.1 mL / cm 2 The precursor film was placed in an environment with a relative humidity of 80% and a hydrolysis temperature of 25°C for hydrolysis for 1 hour, and then placed in a muffle furnace with an air atmosphere, heated to 550°C and sintered for 0.5 hours to obtain a TiO2 seed layer. The combination of the substrate and the TiO2 seed layer was recorded as an intermediate.

[0114] (3) Preparation of TiO2 nanorod array layer:

[0115] Concentrated hydrochloric acid with a mass fraction of 37% and deionized water were mixed in a volume ratio of 1:1 to obtain a hydrochloric acid solution; isopropyl titanate and hydrochloric acid solution were mixed in a volume ratio of 0.5:40 to obtain a hydrothermal reaction solution. The TiO2 seed layer was facing the bottom wall of the reactor, the substrate was facing the opening of the reactor, the entire intermediate was suspended in the reactor, the hydrothermal reaction solution was added to completely immerse the intermediate, and the reactor was sealed, and the hydrothermal reaction was carried out at 180°C for 3h to form a TiO2 nanorod array layer. After the temperature of the reaction system was naturally cooled to room temperature, it was taken out, rinsed with sufficient water and ethanol, and dried to obtain a TiO2 nanorod array film.

[0116] Embodiment 2~5

[0117] Please refer to Table 1, Examples 2 to 5 are basically the same as Example 1, and the differences are as follows:

[0118] Example 2: In step (2), the hydrolysis time is 2 h.

[0119] Example 3: In step (2), the hydrolysis time is 4 h.

[0120] Example 4: In step (2), the hydrolysis time is 8 h.

[0121] Example 5: In step (2), the hydrolysis time is 16 h.

[0122] Embodiment 6~9

[0123] Please refer to Table 1, Examples 6 to 9 are basically the same as Example 3, and the differences are as follows:

[0124] Example 6: In step (2), the relative humidity is 40%.

[0125] Example 7: In step (2), the sintering temperature is 450°C.

[0126] Example 8: In step (3), the reaction time of the hydrothermal reaction is 2 h.

[0127] Example 9: In step (3), the reaction time of the hydrothermal reaction is 4 h.

[0128] Example 10

[0129] In order to verify the importance of density control on the photoelectric performance of thin films, CuInS2 solar cells were prepared using the TiO2 nanorod array films prepared in Examples 2, 3, 4, 8 and 9, respectively, and were marked as devices 1, 2, 3, 4 and 5. The cell preparation method is briefly described as follows: CdS and CuInS2 nanoparticle films are sequentially deposited in the TiO2 nanorod array film to obtain a CuInS2-based heterojunction film; and then a Spiro-OMeTAD hole transport layer and an Au film electrode are sequentially deposited on the CuInS2-based heterojunction film to obtain a solar cell device.

[0130] Test Case

[0131] The TiO2 seed layer and the TiO2 nanorod array layer of each embodiment were tested as follows:

[0132] (1) X-ray diffraction (XRD) test was performed on the TiO2 seed layer in Examples 2 to 4. The results are shown in Figure 3 and Table 2.

[0133] (2) The TiO2 seed layer in Examples 2 to 4 was tested by scanning electron microscope (SEM). The results are shown in Figure 4~Figure 6 and Table 2.

[0134] (3) XRD test was performed on the TiO2 nanorod array layer in Examples 2 to 4. The results are shown in Figure 7 and Table 2.

[0135] (4) SEM test was performed on the TiO2 nanorod array layer in Examples 2 to 4. The results are shown in Figure 8~Figure 10 and Table 2.

[0136] (5) The TiO2 nanorod array layer of Example 3 was tested by high resolution transmission electron microscopy (HRTEM). Fig.11 .

[0137] (6) The photoelectric conversion performance of the solar cell of Example 10 was tested in a laboratory environment. The illumination conditions were: AM 1.5G simulated sunlight, light intensity of 100 mW / cm 2 ; Results Fig.12 and Table 3.

[0138] exist Figure 3~Figure 6 In the embodiment, TiO2(2h), TiO2(4h) and TiO2(8h) correspond to the TiO2 seed layers of Examples 2 to 4, respectively. Figure 7~Figure 10 In the figure, TiO2-NA(2h), TiO2-NA(4h) and TiO2-NA(8h) correspond to the TiO2 nanorod array layers of Examples 2 to 4, respectively.

[0139] like Figure 3 As shown, the solid diamond marks in the figure are characteristic peaks of the anatase

[101] crystal plane, indicating that the crystal form of the nanoparticles in the TiO2 seed layer of Examples 2 to 4 is anatase TiO2.

[0140] like Figure 4~Figure 6 As shown, the thickness of the TiO2 seed layer of Examples 2 to 4 is about 100 nm, the particle size of the nanoparticles in the seed layer is approximately 20 nm to 40 nm, and as the hydrolysis time increases, the particle size of the nanoparticles becomes significantly smaller.

[0141] like Figure 7 As shown, the diffraction peaks at the hollow diamond mark, the hollow inverted triangle mark and the solid inverted triangle mark are characteristic peaks of rutile

[110] ,

[101] and

[002] crystal planes, respectively, indicating that the crystal form of the nanorods in the TiO2 nanorod array layer of Examples 2 to 4 is rutile TiO2.

[0142] like Figure 8~Figure 10 As shown, the TiO2 nanorods extend in a direction away from the substrate, and have a length of about 670nm to 700nm and a diameter of about 30nm to 35nm. The density of the TiO2 nanorods in Examples 2 to 4 is about 95μm -2 、63μm -2 and 25 μm -2 It can be seen that the density of TiO2 nanorods can be regulated by the hydrolysis time of the seed layer; the density of TiO2 nanorods gradually decreases with the extension of the hydrolysis time, but the length and diameter of the TiO2 nanorods are not affected.

[0143] like Fig.11As shown, the TiO2 nanorod array layer of Example 3 has two lattice spacings: d(110)=0.32nm and d(001)=0.29nm, indicating that the TiO2 nanorods are rutile TiO2 single crystals and grow along the

[001] direction.

[0144] like Fig.12 As shown in Table 3, the performance of CuInS2 solar cell devices based on different embodiments is significantly different. The device performance parameters are shown in Table 3, where the open circuit voltage (V oc ) is 0.83V, the short circuit current (J sc ) is 14.56mA / cm 2 , the filling factor (FF) is 55.88%, and the device efficiency (η) reaches 6.78%. V of the CuInS2 solar cell device based on the nanorod array of Example 3 oc 0.82V, J sc Increased to 21.72mA / cm 2 , FF reached 62.18%, η reached 11.10%, it can be seen that after changing the array density, the overall efficiency of the device is significantly improved. V of CuInS2 solar cell device 3 based on nanorod array of Example 4 oc 0.73V, J sc 18.76 mA / cm 2 , FF is 56.11%, and η is 7.68%. The battery experiment results show that only when the density is appropriate can a good array battery efficiency be obtained. In addition, referring to Table 3, by comparing devices 2, 4, and 5, it can be seen that when the density and diameter of the nanorods in the array remain basically unchanged, the length of the nanorods has an important influence on the performance of the solar cell, which in turn affects the precise regulation of the device's photoelectric performance.

[0145] Table 1. Preparation process parameters of TiO2 nanorod array films

[0146]

[0147] Table 2. Structure and properties of TiO2 nanorod array films

[0148]

[0149] Table 3. Performance of solar cells based on TiO2 nanorod array thin films

[0150]

[0151] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0152] The above-described embodiments only express several implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of protection of the present application. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present application, and these all belong to the scope of protection of the present application. Therefore, the scope of protection of the present application shall be subject to the attached claims.

Claims

1. A method for preparing a titanium dioxide nanorod array film, characterized in that: The following steps are involved: mixing titanate, a hydrolysis inhibitor and an organic solvent to obtain a precursor solution; coating the precursor solution on a substrate to obtain a precursor film; The precursor film is subjected to a hydrolysis reaction and sintering treatment to obtain a titanium dioxide seed layer; A titanium dioxide nanorod array layer is formed on the titanium dioxide seed layer by a hydrothermal method.

2. The method for preparing a titanium dioxide nanorod array thin film according to claim 1, characterized in that: The precursor film is subjected to a hydrolysis reaction, comprising the following steps: The precursor film is placed in an environment with a relative humidity of 80% to 90% and a temperature of 10° C. to 40° C. for hydrolysis for 1 h to 32 h.

3. The method for preparing a titanium dioxide nanorod array thin film according to claim 2, characterized in that: One or more of the following conditions are met: (1) The titanate includes one or more of n-butyl titanate, n-propyl titanate, isopropyl titanate and ethyl titanate; (2) The hydrolysis inhibitor includes one or more of acetic acid, hydrochloric acid and nitric acid; (3) The organic solvent includes one or more of ethanol, methanol and isopropanol; (4) The volume ratio of the titanate, the hydrolysis inhibitor and the organic solvent is 1:(0.05-0.2):(2-5).

4. The method for preparing a titanium dioxide nanorod array thin film according to any one of claims 1 to 3, characterized in that: The sintering temperature of the sintering treatment is 450° C. to 550° C., the sintering time is 0.5 h to 2 h, and the sintering atmosphere is an oxidizing atmosphere.

5. The method for preparing a titanium dioxide nanorod array thin film according to claim 4, characterized in that: One or more of the following conditions are met: (1) The crystal form of the nanoparticles in the titanium dioxide seed layer is anatase titanium dioxide; (2) The particle size of the nanoparticles in the titanium dioxide seed layer is 10 nm to 30 nm; (3) The thickness of the titanium dioxide seed layer is 50nm~150nm.

6. The method for preparing a titanium dioxide nanorod array thin film according to any one of claims 1 to 3, characterized in that: The hydrothermal method comprises the following steps: mixing a titanium source and an acid solution to obtain a hydrothermal reaction solution; The titanium dioxide seed layer is placed in the hydrothermal reaction solution to perform a hydrothermal reaction.

7. The method for preparing a titanium dioxide nanorod array thin film according to claim 6, characterized in that: One or more of the following conditions are met: (1) The titanium source includes one or more of n-butyl titanate, n-propyl titanate, isopropyl titanate and ethyl titanate; (2) The acid in the acid solution includes one or more of hydrochloric acid, nitric acid and acetic acid, and the concentration is 1 mol / L to 10 mol / L; (3) The volume ratio of the titanium source to the acid solution is (0.5-1.5): (20-80).

8. The method for preparing a titanium dioxide nanorod array thin film according to claim 6, characterized in that: The reaction temperature of the hydrothermal reaction is 150° C. to 200° C., and the reaction time is 1 h to 5 h.

9. The method for preparing a titanium dioxide nanorod array thin film according to any one of claims 1 to 3, 5 and 7 to 8, characterized in that: The nanorods in the titanium dioxide nanorod array layer meet the following requirements: length of 200nm to 1000nm, diameter of 30nm to 60nm, density of 10μm -2 ~200μm -2 .

10. A titanium dioxide nanorod array film, characterized in that: The titanium dioxide nanorod array film is prepared by the preparation method according to any one of claims 1 to 9.